Early Marriage in Banjarmasin: The Impact on Reproductive Health and Prevention Strategy - R. Topan Aditya Rahman; Esti Yuandari (International Journal of Clinical Inventions and Medical Sciences, 2020)
10% of teenagers by the of aged 15-19 years in Indonesia have become mothers. In fact, getting pregnant at that age has many risks of childbirth complications. The purpose of this study is to determine the causal factors, the impact on reproductive health, and solutions to solving problems of early marriage. The design of this study used a qualitative method with a sample of couples who are married at a young age. Early marriage in the city of Banjarmasin is caused by one's own desires, intimate relationships, and getting pregnant first. Therefore, a strategic step to resolve the problem is through coaching youth and collaboration with the Office of Religious Affairs. Early marriage needs the support and active role of the community for reducing the cases.